Role Play as a Pedagogical Strategy for Cultivating Empathy (GAIMS Journal of Medical Sciences, 2024)
Background: Empathy is considered as the cornerstone of exemplary patient care and training medical graduates in empathy is the most challenging task for the medical educators. The traditional teaching method lacks strength in implementing this skill into the receivers.Aims and Objectives: To explore role play as a pedagogical strategy to provide an immersive learning experience for medical students to capture empathetic principles.Materials and Methods: This observational study was performed in a medical college of South India, among Phase I students. Jefferson scale of empathy was used to quantify empathy level among the participants and following which, they were asked to conduct role play sessions enacting various case scenarios. Post role play session, feedback was taken from the participants as well as the faculty. The empathy scores and the components were compared among males and females using an independent sample t-test and ANOVA respectively.Results: The mean empathy score of the participants were above the cut off points (119.42 ± 9.768). There was no significant difference in total or component wise empathy score among genders, although “putting yourself into patient shoes” was significantly lower when compared to other components (5.93 ± 0.71, 6.29 ±0.52, 4.53 ± 1.35). From the students and teachers’ perspective, role play was an effective method in learning empathy.Conclusions: The facilitators reported organizing role-play sessions to be labor intensive but the insightful reflection of the students far outweighs the effort. In this backdrop, role-play can be considered as an effective teaching method.